Formacion de educadores matematicos en la universidad de Nari no: Etnomatematica y Cognicion - Blanco Alvarez, Hilbert; Marmolejo Avenia, Gustavo A. (Revista SIGMA, 2016)
Abstract This article presents a characterization of the fundamentals of both lines Ethnomathematics and Cognition and its contribution to the training of graduates in mathematics at the University of Nari no. In addition, it exposes contributions in research, social projection and publications in each of these lines. Resumen Se presenta una caracterizacion de los fundamentos de las lneas de Etnomatematica y Cognicion y su aporte a la formacion de Licenciados en Matematicas en la Universidad de Nari no. As mismo, se exponen los aportes en investigacion, proyeccion social y publicaciones en cada una de estas lneas.